Show and Tell Method and Its Application in Improving Speaking Skills - Apriyanto, Sigit; Syakur, Abd (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The ability to speak in Indonesian is a characteristic of a person's ability to understand Indonesian language lessons. After being observed, many students are still not confident in speaking in front of the class or explaining the concept map in a presentation, and even less active class discussions regarding questions and answers. In this case, classroom action research (CAR) provides an effort to improve students' speaking skills by applying the show and tell method by explaining, presenting concept maps, and discussing questions and answers. This study aims to inform that the application of the show and tell method improves the skills of class XI C students at SMK Komputama Majenang. This study was conducted with 2 cycles and as the subject students of class XI C with observation techniques and oral tests with quantitative descriptive analysis. Based on this, the conclusion is that the application of this method can improve speaking skills from the classical 75% passing percentage to 81%. In applying for the show and tell method, the learning steps are the procedures for implementing the show and tell method by the teacher and students. Students provide explanations with instructions in the form of pictures, photos, personal objects, etc. The teacher encourages students to actively discuss the material from the concept map that the teacher provides, encouraging students to ask and answer.